Rancang Bangun Keamanan Jaringan Wireless Yang Terintergrasi Dengan Usermanager Menggunakan Mikrotik (Studi Kasus: DIV Teknik Informatika Politeknik Harapan Bersama) - Wibowo, Dega Surono; Sasmito, Ginanjar Wiro (LPPM Universitas Merdeka Madiun, 2020)
Abstractâ€” For now the internet network is the main requirement of everyone. Now the internet has also reached all elements of society, even in every corner of the place to gather, be it in cafe schools or learning centers, has made the internet the main facility. WiFi is a means to wirelessly connect devices to the internet network. The problem in this research is how to provide a wireless network using the user profile of a hotspot using usermanager. The research method used is by conducting literature studies, using network topology, selecting and configuring network devices, configuring usermanager, conducting testing and analysis of results. Thus the specific target in this research is to design a WIFI network that is integrated with usermanager, and each user can be monitored at any time.Â Keywordsâ€”: Wireless; Hotspot; Usermanager.